Australian Residential Telecommunications Consumption and Substitution Patterns - Madden, gary; Coble-Neal, Grant (Springer Science + Business Media B.V., Formerly Kluwer Academic Publishers B.V., 2005)
Better telecommunications pricing decisions are able to be made when morecomplete information concerning relationships among services is available. This studyanalyses residential fixed-line and mobile telephony, and Internet access and usage demands in an encompassing framework. The discrete-continuous framework allows for service interaction within and between service portfolios. Model estimation is based on the examination of data collected from a country-wide survey of Australian households. In particular, observed service portfolios (household consumption patterns at prevailing access prices and estimated average service usage prices), income and demographic characteristic data are collected. These data also allow the modelling to potentially identify market segments based on income and other household characteristics